A REMARKABLE NEW GYNODIOECIOUS SPECIES OF OCOTEA (LAURACEAE) FROM THE BRAZILIAN ATLANTIC RAIN FOREST, AND ITS PHYLOGENETIC PLACEMENT IN THE OCOTEA COMPLEX - de Moraes, Pedro L. R. [UNESP]; Cardoso, Domingos B. O. S.; Gregório, Bernarda S.; Baitello, João B. (Royal Botanic Garden Edinburgh, 2022)
Ocotea bilocellata Baitello, D.B.O.S.Cardoso & P.L.R.Moraes, a species of Lauraceae that is new to science and from the Atlantic rain forest of the state of São Paulo, Brazil, is described and illustrated. The newly described species does not fit in any of the traditionally circumscribed disporangiate Lauraceae genera; rather, we show that it is phylogenetically placed within the Ocotea minarum group, as revealed by nuclear ribosomal ITS and plastid psbA–trnH sequence data.
Keywords: Atlantic rain forest; Brazil; gynodioecy; Lauraceae; new species; ombrophilous forest; southeast region